Outcomes in prevention and management of miscarriage trials: a systematic review. (11th December 2018) - Smith, PP; Dhillon‐Smith, RK; O'Toole, E; Cooper, NAM; Coomarasamy, A; Clark, TJ
Abstract : Background: There is a substantial body of research evaluating ways to prevent and manage miscarriage, but all studies do not report on the same outcomes. Objective: To review systematically, outcomes reported in existing miscarriage trials. Search strategy: MEDLINE, Embase, CINAHL, and Cochrane were searched from inception until January 2017. Selection criteria: Randomised controlled trials (RCTs) reporting prevention or management of miscarriage. Miscarriage was defined as a pregnancy loss in the first trimester. Data collection and analysis: Data about the study characteristics, primary, and secondary outcomes were extracted. Main results: We retrieved 1553 titles and abstracts, from which 208 RCTs were included. For prevention of miscarriage, the most commonly reported primary outcome was live birth and the top four reported outcomes were pregnancy loss/stillbirth ( n  = 112), gestation of birth ( n  = 68), birth dimensions ( n  = 65), and live birth ( n  = 49). For these four outcomes, 58 specific measures were used for evaluation. For management of miscarriage, the most commonly reported primary outcome was efficacy of treatment. The top four reported outcomes were bleeding ( n  = 186), efficacy of miscarriage treatment ( n  = 105), infection ( n  = 97), and quality of life ( n  = 90). For these outcomes, 130 specific measures were used for evaluation. Conclusions: Our review found considerable variation in the reporting of primary and secondary outcomes along with the measures used to assess them. There is a need for standardised patient‐centred clinical outcomes through the development of a core outcome set; the work from this systematic review will form the foundation of the core outcome set for miscarriage. Tweetable abstract: There is disparity in the reporting of outcomes and the measures used to assess them in miscarriage trials. Tweetable abstract: There is disparity in the reporting of outcomes and the measures used to assess them in miscarriage trials.